Maraviroc as a potential HIV-1 latency-reversing agent in cell line models and ex vivo CD4 T cells. (13th January 2021) - Vicenti, Ilaria; Dragoni, Filippo; Monti, Martina; Trombetta, Claudia Maria; Giannini, Alessia; Boccuto, Adele; Saladini, Francesco; Rossetti, Barbara; De Luca, Andrea; Ciabattini, Annalisa; Pastore, Gabiria; Medaglini, Donata; et al.
Abstract : Recent studies have suggested that the CCR5 antagonist maraviroc (MVC) may exert an HIV-1 latency reversal effect. This study aimed at defining MVC-mediated induction of HIV-1 in three cell line latency models and in ex vivo CD4 T cells from six patients with suppressed viraemia. HIV-1 induction was evaluated in TZM-bl cells by measuring HIV-1 LTR-driven luciferase expression, and in ACH-2 and U1 latently infected cell lines by measuring cell-free (CFR) and cell-associated (CAR) HIV-1 RNA by qPCR. NF- κ B p65 was quantified in nuclear extracts by immunodetection. In ex vivo CD4 T cells, CAR, CFR and cell-associated DNA (CAD) were quantified at baseline and 1–7–14 days post-induction (T1, T7, T14). At T7 and T14, the infectivity of the CD4 T cells co-cultured with MOLT-4/CCR5 target cells was evaluated in the TZM-bl assay (TZA). Results were expressed as fold activation (FA) with respect to untreated cells. No LTR activation was observed in TZM-bl cells at any MVC concentration. NF- κ B activation was only modestly upregulated (1.6±0.4) in TZM-bl cells with 5 µM MVC. Significant FA of HIV-1 expression was only detected at 80 µM MVC, namely on HIV-1 CFR in U1 (3.1±0.9; P =0.034) and ACH-2 cells (3.9±1.4; P =0.037). CFR was only weakly stimulated at 20 µM in ACH-2 (1.7±1.0 FA) cells and at 5 µM in U1 cells (1.9±0.5 FA). Although no consistent pattern of MVC-mediated activation was observed in ex vivo experiments, substantial FA values were detected sparsely on individual samples with different parameters. Notably, in one sample, MVC stimulated all parameters at T7 (2.3±0.2 CAD, 6.8±3.7 CAR, 18.7±16.7 CFR, 7.3±0.2 TZA). In conclusion, MVC variably induces HIV-1 production in some cell line models not previously used to test its latency reversal potential. In ex vivo CD4 T cells, MVC may exert patient-specific HIV-1 induction; however, clinically relevant patterns, if any, remain to be defined.